Two Decades of Match-Mismatch in Northeast Arctic Cod – Feeding Conditions and Survival - Endo, Clarissa Akemi Kajiya; Stige, Leif Christian; Skogen, Morten D.; Ciannelli, Lorenzo; Vikebø, Frode V. (Frontiers in Marine Science, 2022)
The successful recruitment of Northeast Arctic (NEA) cod is thought to depend on sufficient and suitable prey for the newly hatched larvae, in particular the nauplii stages of the lipid-rich calanoid copepod species Calanus finmarchicus. The role of spatial and temporal variations in prey availability in combination with temperature and other factors in influencing growth and survival of cod larvae is, however, incompletely understood. By combining an individual based model for NEA cod larvae at the Norwegian coast with a high-resolution ocean model and a nutrient-phytoplankton-zooplankton-detritus model providing 18 years of daily environmental conditions and prey availability we assessed larval growth and survival until they settle in their feeding habitat in the Barents Sea in early fall. We find on average a two-week delay from the peak timing of first-feeding cod larvae to the peak in prey availability. In warm years, more larvae experience food limitation than in normal years. The positive effects of high temperature on growth, survival and ultimately recruitment are nonetheless larger than the negative effects of food limitation. Food limitation mainly affects larvae spawned in southern areas or late in the spawning season as these larvae experience the highest temperatures and have the highest energy requirements. Our findings highlight the spatial and temporal differences in mechanisms that regulate growth and survival of early life stages of NEA cod and suggest that spatially resolved data may be essential for understanding match-mismatch dynamics.